Nuance and behavioral cogency: How the Visible Burrow System inspired the Stress-Alternatives Model and conceptualization of the continuum of anxiety - Robertson, James M. (Physiol Behav, 2015)
By creating the Visible Burrow System (VBS) Bob Blanchard found a way to study the interaction of genetics, physiology, environment, and adaptive significance in a model with broad validity. The VBS changed the way we think about anxiety and affective disorders by allowing the mechanisms which control them to be observed in a dynamic setting. Critically, Blanchard used the VBS and other models to show how behavioral systems like defense are dependent upon context and behavioral elements unique to the individual. Inspired by the VBS, we developed a Stress Alternatives Model (SAM) to further explore the multifaceted dynamics of the stress response with a dichotomous choice condition. Like the VBS, the SAM is a naturalistic model built upon risk-assessment and defensive behavior, but with a choice of response: escape or submission to a large conspecific aggressor. The anxiety of novelty during the first escape must be weighed against fear of the aggressor, and a decision must be made. Both outcomes are adaptively significant, evidenced by a 50/50 split in outcome across several study systems. By manipulating the variables of the SAM, we show that a gradient of anxiety exists that spans the contextual settings of escaping an open field, escaping from aggression, and submitting to aggression. These findings correspond with increasing levels of corticosterone and increasing levels of NPS and BDNF in the central amygdala as the context changes. Whereas some anxiolytics were able to reduce the latency to escape for some animals, only with the potent anxiolytic drug antalarmin (CRF1R-blocker) and the anxiogenic drug yohimbine (α(2) antagonist) were we able to reverse the outcome for a substantial proportion of individuals. Our findings promote a novel method for modeling anxiety, offering a distinction between low-and-high levels, and accounting for individual variability. The translational value of the VBS is immeasurable, and it guided us and many other researchers to seek potential clinical solutions through a deeper understanding of regional neurochemistry and gene expression in concert with an ecological behavioral model.